IZO or IOH Window Layers Combined with Zn(O, S) and CdS Buffers for Cu(In, Ga)Se2 Solar Cells. Issue 12 (6th November 2017) - Witte, Wolfram; Carron, Romain; Hariskos, Dimitrios; Fu, Fan; Menner, Richard; Buecheler, Stephan
Abstract : CdS and Zn(O, S) grown by chemical bath deposition are well‐established buffer materials for Cu(In, Ga)Se2 (CIGS) thin‐film solar cells and modules. Typically these buffers were combined with a ZnO:Al (AZO) or ZnO:B window layer and i‐ZnO or (Zn, Mg)O as high‐resistive interlayer. Nowadays, alternative transparent conductive oxide (TCO) materials with higher mobility as compared to AZO like indium zinc oxide (IZO) and hydrogen‐doped indium oxide (IOH) are under investigation. In the present contribution, we report on the performance of CIGS cells with solution‐grown Zn(O, S) or CdS buffer layers in combination with different stacking sequences including i‐ZnO, (Zn, Mg)O, IZO, and IOH. Devices with the commonly used AZO window layer are used as references. Efficiencies above 16% without anti‐reflective coating (ARC) are achieved for cells with Zn(O, S)/(Zn, Mg)O combined with IZO, IOH, and AZO whereas poor results are obvious with all Zn(O, S)/i‐ZnO combinations. Nevertheless, CdS‐buffered reference cells with the different TCO materials exhibit efficiencies in the range of 17–18% without ARC mainly due to higher open‐circuit voltages. Abstract : This contribution reports on the performance of Cu(In, Ga)Se2 (CIGS) thin‐film solar cells with solution‐grown Zn(O, S) or CdS buffer layers in combination with different stacking sequences including i‐ZnO, (Zn, Mg)O, indium zinc oxide (IZO), hydrogen‐doped indium oxide (IOH), and ZnO:Al (AZO). Efficiencies above 16% are achieved for CIGS solar cells with Zn(O, S)/(Zn, Mg)O combined with all transparent conductive oxides (TCO).